2020
DOI: 10.1111/hex.13089
|View full text |Cite
|
Sign up to set email alerts
|

Living with opioids: A qualitative study with patients with chronic low back pain

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The higher prevalence in the studies based on health registries could be explained because these patients are usually treated in specialized pain units, especially those patients with complex types of pain conditions who do not respond to conventional treatment and require special drugs, such as opioids ( Henderson et al, 2013 ; Pérez et al, 2013 ; De Sola et al, 2020 ). Furthermore, a lack of healthcare providers offering effective treatment alternatives is likely to have an impact on other treatment choices ( White et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher prevalence in the studies based on health registries could be explained because these patients are usually treated in specialized pain units, especially those patients with complex types of pain conditions who do not respond to conventional treatment and require special drugs, such as opioids ( Henderson et al, 2013 ; Pérez et al, 2013 ; De Sola et al, 2020 ). Furthermore, a lack of healthcare providers offering effective treatment alternatives is likely to have an impact on other treatment choices ( White et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, despite the lack of information on the efficacy of opioids ( Warner, 2012 ), the introduction of high-dose and extended-release oral tablet formulations of opioids has been shown to increase the total prescriptions among CNCP patients, especially in the last decade ( Von Korff et al, 2011 ; Alam and Juurlink, 2015 ; Severino et al, 2018 ). In some European countries, such as Spain, the use of opioids increased by 83.59% from 2008 to 2015 ( De Sola et al, 2020 ). Additionally, in 2016, more than one-third of adults were prescribed opioids in the United States ( Walker, 2018 ), making it an important social problem ( Sehgal et al, 2012 ; Salazar et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…63 A study among pain patients using opioids found that these patients often gave priority to pain relief even though they could aspire to quit opioids. 64 Regarding providers, a study in the field of mental health highlighted their dilemmas in the face of treatment-related harms, and their discursive strategies to value treatment benefits rather than adverse effects. 65 Our findings underscored discrepancies between pharmacists' and patients' opinions regarding both the prioritization of adverse effects affecting the quality of life versus those presenting potential future harms, and the prioritization of adverse effect prevention versus pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…38,41 The impacts of pain on patients' lives have been shown to be often underestimated in clinical settings, as the invisibility of pain can create misunderstandings and reduce providers' empathetic behaviours. 3,64,68 It is essential to support pharmacists' practices with chronic pain patients through better training on pain assessment and recognition. Training initiatives promoting shared decision-making could help tailor treatments to patients' expectations and needs while minimizing the risks associated with adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…12 Many patients whose pain is not substantially reduced by low back surgeries, irrespective of the reason, have few treatment options other than chronic opioid therapy. That there exists a copious body of literature demonstrating that opioid reliance exacerbates the stigmatization and marginalization [13][14][15][16][17] of these patients is not surprising. Society uses a number of unflattering terms for those who are opioid-dependent, irrespective of whether they are medical or recreational users.…”
mentioning
confidence: 99%